Relation of Children's Dietary Reporting Accuracy to Cognitive Ability - Smith, Albert F. (Oxford University Press, 2011)
A validation study of children's dietary reporting provided an opportunity to investigate whether cognitive ability is a source of systematic error in dietary recalls. From the fall of 2004 through the spring of 2007, fourth-grade children (n = 374) in Columbia, South Carolina, were observed eating school meals and interviewed to obtain 24-hour dietary recalls; subsequently, measures of dietary reporting error were calculated. The common factor extracted from 4 subject-area achievement tests (scores on which were provided by the school district for 362 children) was used as a measure of cognitive ability. For the 325 children who reported school meals that met the criteria to be reports about school meals, as cognitive ability increased, dietary reporting error decreased; the relation between cognitive ability and dietary reporting performance was stronger among girls than among boys. The mean cognitive ability for 37 children who reported no meals that satisfied the criteria for being reports about school meals was significantly lower than that for the 325 children who reported meals that satisfied these criteria. These findings indicate that cognitive ability is a source of systematic error in children's dietary recalls. More generally, the quality of epidemiologic survey data may depend systematically on the cognitive ability of respondents.